Analisis Pengamanan Jaringan Menggunakan Router Mikrotik dari Serangan DoS dan Pengaruhnya Terhadap Performansi - Arief Indriarto Haris; Budhi Riyanto; Farry Surachman; Ardito Adi Ramadhan (Komputika : Jurnal Sistem Komputer, 2022)
Denial of Service (DoS) is a serious cyber threat and has a destructive impact because it makes target unavailable by flooding large amounts of traffic. The router as a gateway plays a vital role in the network, if its function is disrupted it will have a direct impact on the overall network performance. This study aims to analyze of securing network from DoS using a mikrotik router by utilizing the built-in security features and assessing the level of effectiveness. By using the PPDIOO methodology, there are six router conditions tested against DoS with five indicators being measured. The results obtained are that the security with firewall raw in condition 6 is the most effective and efficient compared to other conditions. CPU consumption has been reduced by 20% and the ping response time has returned to normal, and the detection and blocking process has been automated. However, all security with built-in security features is considered ineffective in dealing with DoS, because it is proven that CPU consumption is still high, DoS traffic cannot be eliminated, only latency can be normalized.